Managing Morality and Building “Balance”: Depoliticisation as Management in Canada’s Federal Response to R. v. Morgentaler - Vachon, Rebecca (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2020)
In 1988, Canada’s federal Parliament faced the challenge of addressing the legal status of abortion after the Supreme Court of Canada, in R. v. Morgentaler, struck down existing restrictions. In the resulting legal void, the Progressive Conservative (PC) federal government found itself under pressure to act. Examining parliamentary debates and recently released cabinet documents from the period of January 1988 to May 1990, this paper asks how the federal government managed the abortion issue following R. v. Morgentaler, including creating and defending legislation as a policy solution. This paper identifies politicising and depoliticising procedures (i.e., legislation and motions) that framed the issue in a way that that allowed the government to take action on the abortion issue while maintaining distance as it crafted and defended legislation. This paper reconstructs the frames that presented government legislation (Bill C-43) as “balanced” and uses the theoretical concepts of politicisation and depoliticisation to show how the frames alternately pushed and pulled the government towards and away from the abortion issue. These frames worked by deferring responsibility to other levels of government and the private sphere, as well as by invoking fatalism by highlighting the intransigency of abortion, the constraints that limit government action, and the necessity of pursuing only the government’s proposed solution. Although the frames serve to justify the frame of a “balanced” solution, their inherent contradictions and tensions point to fractures within the narrative of Bill C-43 as a “balanced” solution and may help explain the legislation’s failure.